2013
DOI: 10.1111/febs.12111
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐1 modulates β‐integrin‐dependent and interleukin‐6‐dependent functions in breast cancer cell adhesion, migration, and resistance to irradiation

Abstract: Syndecan-1 is a cell surface heparan sulfate proteoglycan with various biological functions relevant to tumor progression and inflammation, including cell-cell adhesion, cell-matrix interaction, and cytokine signaling driving cell proliferation and motility. Syndecan-1 is a prognostic factor in breast cancer, and has a predicitive value for neodadjuvant chemotherapy. It is still poorly understood how syndecan-1 integrates matrix-dependent and cytokine-dependent signaling processes in the tumor microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 69 publications
3
122
1
1
Order By: Relevance
“…Modulation of a 5 b 1 integrins by syndecan-1 was also reported during focal adhesion formation and migration [18][19][20]. Interestingly, the latter pathway can either enhance or suppress these processes [18][19][20]. Further, activation of focal adhesion kinase (FAK) and Rho GTPase has been implicated in syndecan-1-mediated effects on cell migration [16,21].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Modulation of a 5 b 1 integrins by syndecan-1 was also reported during focal adhesion formation and migration [18][19][20]. Interestingly, the latter pathway can either enhance or suppress these processes [18][19][20]. Further, activation of focal adhesion kinase (FAK) and Rho GTPase has been implicated in syndecan-1-mediated effects on cell migration [16,21].…”
Section: Introductionmentioning
confidence: 93%
“…In addition, syndecan-1 can act as regulator of a v b 3 and a v b 5 integrin activation [15,17]. Modulation of a 5 b 1 integrins by syndecan-1 was also reported during focal adhesion formation and migration [18][19][20]. Interestingly, the latter pathway can either enhance or suppress these processes [18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies showed that sdc1 knockdown in breast cancer cells increased their migration rate on FNcoated surfaces in a manner that was dependent on a 5 b 1 -or a v -containing integrins. 66 Whether similar results would be seen if cells were grown on LN332-coated surfaces is unknown.…”
mentioning
confidence: 91%
“…As highly glycosylated, sulfated molecules and, hence, negatively charged molecules, they have a large capacity to bind to other charged molecules such as cytokines and chemokines (2) and have been implicated in the presentation of cytokines to cells (3)(4)(5) and in the activation of integrin receptors (6)(7)(8). Syndecans are the best studied class of cell surface heparan sulfate proteoglycans (9); they exist in four different forms, syndecan 1-4, all of which consist of a core protein containing an ectodomain (extracellular domain), which carries the glycosylation sites, a transmembrane domain and a cytoplasmic domain.…”
mentioning
confidence: 99%